Desafíos de la política criminal peruana de mano blanda frente a la criminalidad organizada de cuello blanco - Chanjan Documet, Rafael (2025)
In the midst of the current context of crime expansion in Peru, this article aims to analyze the link between organized crime, corruption and money laundering. To this end, the essential characteristics and typologies of organized crime and the relationship with “white collar” crimes in the Peruvian environment are addressed. Likewise, a critical analysis of Peruvian criminal policy in the face of “white collar” organized crime is carried out, with special emphasis on secondary criminalization, warning of a tendency of “soft hand” or less rigor of the state’s punitive power in the face of this phenomenon.